Cystic Fibrosis - Dolan, Mary (Res Medica, 2014)
Cystic fibrosis, a genetic disease with an autosomal recessive mode of inheritance, was first described in 1936 by Fanconi et al. He described the disease in a paper entitled The Coeliac Syndrome with congenital cystic pancreatic fibromatosis and bronchietasis. Since then the disease has been known by various names such as Cystic Fibrosis of the Pancreas, Mucoviscidoses, fibrosis of the pancreas until it was shortened to Cystic Fibrosis in the 1960s. Cystic Fibrosis represents the commonest autosomal recessive disorder in Caucasian populations. The mutant gene, recently identified on the long arm of chromosome 7 has a carrier rate equal to 1 in 22 among Caucasians. The overall incidence of the disease in 1 per 2000 live births. However it has a much lower incidence amongst non- Caucasian populations. Amongst the UK population there are 5000 cystic fibrosis sufferers. Slightly more than 300 affected babies are born annually. The disease affects many tissues, especially the endocrine glands. It results in the production of abnormally viscous secretions which cause duct obstruction and are therefore responsible for pancreatic insufficiency, malabsorption syndromes, biliary cirrhosis and male infertility. The lungs of cystic fibrosis patients are found to be normal at birth but are very prone to infection. Recurrent infection is responsible for the irreversible secondary lung damage which is usually responsible for the shortened life expectancy of cystic fibrosis patients. Death usually results from a severe bacterial pneumonia or is related to the development of cor pulmonale from lung disease.